PENGEMBANGAN E-BOOKLET KERAGAMAN FAMILI ASTERACEAE DI TAMAN BIODIVERSITAS HUTAN HUJAN TROPIS MANDIANGIN - Rahilah Rahilah; Sri Amintarti; Amalia Rezeki (Jurnal Education and Development, 2023)
The Asteraceae family has thousands of species and mostly found in the surrounding environment so that it can be used as a source of learning. Research and development of teaching materials in the form of e-booklets on diversity of the Asteraceae Family in the Taman Biodiversitas Hutan Hujan Tropis Mandiangin as teaching materials on biological diversity in biology aims to describe the suitability, feasibility and readability of e-Booklet development. This study uses a 4-D model with four steps which are limited to the Develop stage according to Thiagarajan et al. (1974). The developes e-Booklet was tested for suitability and appropriateness by three experts (two supervisors and one Biology teacher at SMA Negeri 12 Banjarmasin), as well as a readability trial conducted by six students from SMA Negeri 12 Banjarmasin. The development of e-Booklet teaching materials for diversity of the herbaceous Asteraceae Family in Taman Biodiversitas Hutan Hujan Tropis Mandiangin obtained a suitability score of 4.68, which means that the processed e-Booklet is very appropriate, the eligibility value with a score of 4,52, it means the processed e-Booklet very feasible, and the readability value with score 4,61 which means that the e-Booklet is processed very well so that it is practical for students to use.